2005
DOI: 10.1097/01.ta.0000141890.29032.9a
|View full text |Cite
|
Sign up to set email alerts
|

Effect From Multiple Episodes of Inadequate Empiric Antibiotic Therapy for Ventilator-Associated Pneumonia on Morbidity and Mortality Among Critically Ill Trauma Patients

Abstract: Critically ill trauma patients experiencing multiple episodes of IEAT for VAP have increased morbidity and mortality. These findings reinforce the importance of developing and refining a unit-specific pathway for the empiric management of VAP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 26 publications
3
41
0
Order By: Relevance
“…The nosocomial bacteria that usually cause VAP tend to be more antibiotic resistant (306). Ramzy and colleagues (356) demonstrated that although the organisms colonizing the burn wound were similar to those recovered from quantitative culture of bronchoalveolar lavage fluid samples in pediatric burn patients with VAP, quantitative wound culture was not predictive of cross-infection in the lung.…”
Section: Pneumoniamentioning
confidence: 99%
See 1 more Smart Citation
“…The nosocomial bacteria that usually cause VAP tend to be more antibiotic resistant (306). Ramzy and colleagues (356) demonstrated that although the organisms colonizing the burn wound were similar to those recovered from quantitative culture of bronchoalveolar lavage fluid samples in pediatric burn patients with VAP, quantitative wound culture was not predictive of cross-infection in the lung.…”
Section: Pneumoniamentioning
confidence: 99%
“…Burn patients with severe inhalation injury requiring prolonged intubation are also at risk for developing ventilator-associated pneumonia (VAP) (35,86,306,378,431,445,446). VAP is defined as pneumonia that develops more than 48 h after intubation (e.g., late onset) in a mechanically ventilated patient who had no signs of this complication at the time the endotracheal tube was inserted.…”
Section: Pneumoniamentioning
confidence: 99%
“…Unit-specific antibiograms also may reduce the likelihood of inappropriate prescribing of empiric therapy, which correlates with poor clinical outcomes [24]. In our S/TICU, the unit-specific antibiogram led to changes in empiric antimicrobial choices for patients with suspected HAP/VAP.…”
Section: Discussionmentioning
confidence: 94%
“…In hospital-acquired pneumonia or ventilatorassociated pneumonia, inadequate empirical treatment is associated with high costs, morbidity, and mortality (2,9,17,18). In one study of adult trauma patients who experienced more than one ventilator-associated pneumonia episode for which inadequate empirical treatment was received, almost half of patients died (21). Clearly, the emergence and continued spread of antibiotic resistance require the introduction of new broad-spectrum antimicrobials that can improve outcomes, reduce the economic and medical burdens of MDR strains, and limit further development of resistance.…”
Section: Discussionmentioning
confidence: 99%